2019
DOI: 10.3390/rs11212489
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emission Estimates by the Global High-Resolution Inverse Model Using National Inventories

Abstract: We present a global 0.1 • × 0.1 • high-resolution inverse model, NIES-TM-FLEXPART-VAR (NTFVAR), and a methane emission evaluation using the Greenhouse Gas Observing Satellite (GOSAT) satellite and ground-based observations from 2010-2012. Prior fluxes contained two variants of anthropogenic emissions, Emissions Database for Global Atmospheric Research (EDGAR) v4.3.2 and adjusted EDGAR v4.3.2 which were scaled to match the country totals by national reports to the United Nations Framework Convention on Climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 63 publications
4
46
0
Order By: Relevance
“…Here, we reported the results of our analysis using a high-resolution global Eulerian-Lagrangian coupled inverse model of methane using national reports of anthropogenic methane emissions to the United Nations Framework Convention on Climate Change (UNFCCC) ( [23]) as prior anthropogenic fluxes and evaluated the posterior emissions optimized in two emission categories of natural and anthropogenic on a country scale. This study is an extension to one by Wang et al (2019) [24], where they compared methane emissions for 2010-2012 for large regions with UNFCCC reports using either Emission Database for Global Atmospheric Research (EDGAR) or UNFCCC reported values as prior, whereas, in this study, we reported results for country-scale analysis of methane emissions for 2011-2017, with more detailed discussion and use of independent validation for India using optimized forward simulations of aircraft CH 4 observations.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Here, we reported the results of our analysis using a high-resolution global Eulerian-Lagrangian coupled inverse model of methane using national reports of anthropogenic methane emissions to the United Nations Framework Convention on Climate Change (UNFCCC) ( [23]) as prior anthropogenic fluxes and evaluated the posterior emissions optimized in two emission categories of natural and anthropogenic on a country scale. This study is an extension to one by Wang et al (2019) [24], where they compared methane emissions for 2010-2012 for large regions with UNFCCC reports using either Emission Database for Global Atmospheric Research (EDGAR) or UNFCCC reported values as prior, whereas, in this study, we reported results for country-scale analysis of methane emissions for 2011-2017, with more detailed discussion and use of independent validation for India using optimized forward simulations of aircraft CH 4 observations.…”
Section: Introductionmentioning
confidence: 70%
“…The top fifteen emitting countries based on EDGAR v4.3.2 estimate for 2012 and other four countries Germany, France, United Kingdom, and Japan were selected to adjust the inventory according to UNFCCC reports (see Table A2). These nineteen countries emit 66% of the global total methane for the year 2012 ( [24]). The new gridded prior emission based on the UNFCCC reports was produced by scaling the annual total to EDGAR v4.3.2 values.…”
Section: Prior Fluxesmentioning
confidence: 99%
See 3 more Smart Citations